Analisis Kinerja Pemasangan Baterai Lithium Ion dan Ultra Kapasitor Pada Pembangkit Listrik Tenaga Surya - Makmur Saini; Muhammad Ruswandi Djalal; Rustang Rustang; Deum Patria F Abbas; Yusril Has Barlian (Jurnal Sinergi Jurusan Teknik Mesin, 2022)
Batteries are components that supply, provide and distribute electrical energy in various electronic devices. Still, there are times when the battery must be recharged because the battery has a high energy storage ratio but has limited power. Another component that functions like a battery is a supercapacitor which can store a large charge of energy that can be used to help battery performance. This study aimed to analyze the impact of installing supercapacitors on batteries operating in solar power plants by varying the number of supercapacitors connected to batteries. The methods used in this research are literature study, design method, manufacturing method, testing method, and data analysis method. Based on the test results, it was found that the installation of 4 capacitors has optimal performance, with an average current consumption of 0.18877551 Ampere. For three capacitors, the average current is 0.203552632 Ampere. For two capacitors, the average current is 0.205517241 Ampere. As for the power characteristics, for four capacitors, the average power is 31.81632653 watts. With three capacitors, the average power is 34.36447368 Watt, and with two capacitors, 34.71724138 Watt.